Use of pectin in pharmaceutical technology [Pektin'in farmasotick teknolojide kullanimi] - (:unkn) unknown (My University, 2000)
Pectin is a natural polysaccharide obtained from apple pomace or rind of citrus fruits and is being used increasingly in pharmaceutical technology studies. In this paper, information about the physical, chemical and pharmacological properties of pectin are given. There is also information about its application in different areas, especially in pharmaceutical technology.
Keywords: Natural polysaccharide; Pectin